IL33-induced neutrophil extracellular traps (NETs) mediate a positive feedback loop for synovial inflammation and NET amplification in rheumatoid arthritis - Jifeng Tang; Jinfang Xia; Huali Gao; Renquan Jiang; Lianbo Xiao; Huiming Sheng; Jinpiao Lin (Experimental and Molecular Medicine)
Abstract This study investigated the mechanisms driving the induction and sustained presence of neutrophil extracellular traps (NETs) in the synovial microenvironment of rheumatoid arthritis (RA). Synovial tissue and fluid samples were collected from patients with RA and osteoarthritis (OA), and NET levels and cytokine concentrations were measured using a cytometric bead array and enzyme-linked immunosorbent assay (ELISA). The ability of interleukin-33 (IL-33) to induce NET formation was evaluated using quantitative assays, immunofluorescence staining, live-cell imaging, and electron microscopy. Coincubation experiments of NETs with fibroblast-like synovial cells (FLSs) were conducted, and a modified Transwell migration assay was designed to assess neutrophil migration. The role of IL-33 and NETs in RA progression was further investigated using a collagen antibody-induced arthritis (CAIA) mouse model. The results revealed an increase in NETs and IL-33 levels in the synovial fluid of RA patients, with a significant positive correlation between them. NET formation assays confirmed that IL-33 activates neutrophils to produce NETs and that neutrophils from RA patients exhibit increased responsiveness to IL-33 stimulation. Both in vitro and in vivo evidence has demonstrated that NETs stimulate FLSs to secrete IL-33 and the chemokine CXCL8 via Toll-like receptor 9, promoting further neutrophil recruitment and increasing NET production within the RA synovium. This study reveals a novel positive feedback loop involving NETs and FLSs that is mediated by IL-33 that increases NET accumulation in RA. Targeting IL-33 or NET formation and amplification may offer new therapeutic strategies for managing RA.